2018
DOI: 10.1111/jcpe.12997
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported oral health predicts tooth loss after five and ten years in a population‐based study

Abstract: Self-reported oral health provides reliable predictions of tooth loss comparable to those assessed by clinical diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…In a previous report, we demonstrated that clinical indicators of oral health namely, number of teeth and, to a lesser degree, periodontal disease are associated with frailty index among older Americans after adjusting for inadequate nutritional intake and important covariates similar to the results observed with self‐rated oral health in this study 23 . This can be explained as self‐rated oral health is associated with clinical measures of oral health, 11 and predict five‐year and ten‐year tooth loss 24 . Therefore, self‐rated oral health reflects to some extent the previously evaluated associations between clinical oral health indicators and frailty 25 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In a previous report, we demonstrated that clinical indicators of oral health namely, number of teeth and, to a lesser degree, periodontal disease are associated with frailty index among older Americans after adjusting for inadequate nutritional intake and important covariates similar to the results observed with self‐rated oral health in this study 23 . This can be explained as self‐rated oral health is associated with clinical measures of oral health, 11 and predict five‐year and ten‐year tooth loss 24 . Therefore, self‐rated oral health reflects to some extent the previously evaluated associations between clinical oral health indicators and frailty 25 .…”
Section: Discussionsupporting
confidence: 83%
“…23 This can be explained as self-rated oral health is associated with clinical measures of oral health, 11 and predict five-year and ten-year tooth loss. 24 Therefore, selfrated oral health reflects to some extent the previously evaluated associations between clinical oral health indicators and frailty. 25 The psychosocial impact of poor oral health on loneliness, socialisation, 26 self-consciousness and embarrassment, 27 and depressive symptoms among older adults, 28,29 should also be considered as a possible link for the observed association in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical oral health measures are much more expensive and difficult to conduct in large populations and thus are often unfeasible. Nonetheless, SROH has been reported to be associated with various extents with numerous clinical indicators of oral health such as number of decayed teeth, missing teeth, future tooth loss and periodontal health status 18‐22 …”
Section: Methodsmentioning
confidence: 99%
“…Poor oral self‐care and non‐compliance go along with periodontitis progression and tooth loss (König, Plagmann, Langenfeld, & Kocher, ). Moreover, ensuring an adequate level of periodontal awareness in the community would improve the reliability of the widely used self‐reported oral health questionnaires in epidemiological investigations (Meisel, Holtfreter, Völzke, & Kocher, ), as individuals reporting having periodontal disease are usually right (Airila‐Mansson, Söder, Jin, Söder, & Klinge, ).…”
Section: Introductionmentioning
confidence: 99%